Eating behaviours and the workplace: the role of socioeconomic and sociodemographic characteristics - Grant, Judith (2018)
The overall aim of the research described in this thesis is to explore the role of socioeconomic status (SES) (defined in terms of education, salary, and job grade) and demographic and personal factors (including age, weight, number of dependants, and gender) in relation to the eating behaviours of employees, and to explore barriers and facilitators to healthy eating in the workplace. The purpose of examining these issues in the workplace is to better enable practitioners to develop interventions designed to assist workers in the adoption of healthy eating behaviours.